Training periodization for a world-class 400 meters individual medley swimmer - González-Ravé, José María; B. Pyne, David; Castillo, José; González-Mohíno, Fernando; Stone, Michael (Biology of Sport, 2022)
We present a case study of the periodized training by a world-class 400-m Individual Medley (IM) swimmer (4th in 2019 World Championships) in the season leading to a bronze medal in the 2018 European Championship. The complexity of this IM preparation was based on the experiences, observations and innovations of an Olympic swimming coach. Over 52 weeks, a traditional periodization model was employed using three macrocycles. A total of 15 competitions were completed in the season increasing in frequency in the third macrocycle. The training intensity distribution (TID) followed the pattern of a traditional pyramidal model in general training and polarized and threshold models during specifictraining before competitions. Weekly training volume ranged from 25 to 79 km, 24 to 87 km, and 25 to 90 km in each of the three macrocyles. Altitude training comprised 23% of total training weeks. Haemoglobin [Hb] increased from 14.9 to 16.0 g/100 ml and haematocrit from 45.1 to 48.1% after altitude training. Heart rate (HR) and [La- ] decreased at submaximal swimming intensities, while swimming velocity increased in the 8×100 m incremental swimming test in A2(1.4%) and in AT (0.6%). Pull up power was increased 10% through the season.